Comparative analysis of the mobilome yields new insights into its diversity, dynamics and evolution in parasites of the Trypanosomatidae family - Percy Omar Tullume-Vergara; Adriana Ludwig; Vyacheslav Yurchenko; Adriano Cappellazzo Coelho; Elizabeth Magiolo Coser; Marco Aurélio Krieger; Marta M.G. Teixeira; Jeffrey Jon Shaw; Joao M.P. Alves (Parasitology)
Transposable elements (TEs) have the ability to move and amplify inside the host genome, making them a pivotal source of genome plasticity. Presently, only 4 TE clades (all classified as Class I retrotransposons) have been identified in trypanosomatids. We predicted repeat content and manually curated TEs across the genomes of 57 trypanosomatids, shedding light on their proportions, diversity and dynamics. Our analysis yielded 214 TE consensus sequence models across the dataset, with abundance ranging from 0.1% to 7.2%. We found evidence of recent transposon activity in most species, with notable bursts in the Vickermania, Lafontella, Porcisia and Angomonas spp., along with Leishmania (Mundinia) chancei, L. (M.) orientalis and L. (M.) procaviensis. We confirmed that the 4 TE clades have colonized virtually all lineages of trypanosomatids, potentially playing a role in shaping their genome architecture. The effort of this work culminated in the establishment of the Trypanosomatid TE Database 1.0, a resource designed to standardize the TE annotation process that can serve as a foundation for future studies on trypanosomatid TEs.